DESCRIPTION OF DIFFICULTY ON ELECTRICITY AND MAGNETISM CONCEPTS OF PHYSICS EDUCATION STUDENTS AMONG CROSS ACADEMIC LEVEL - Wardana, Rendy Wikrama; Liliasari, Liliasari; Tjiang, Paulus Tjahyono; Nahadi, Nahadi (Journal of Science Education Research, 2019)
Some previous studies have shown that electricity and magnetism is one of the concepts of abstract, difficult, and complex. The purpose of the research illustrates the difficulties of academic cross-level physics education students on magnetic electrical concepts. Research used qualitative descriptive methods. The number of research samples is 103 students consisting of 73 the third year Bachelor?s Students of Physics Education and 30 Master?s Students of Physics Education in one of State University in Bandung City. Research instruments used essay-shaped tests and interview guides. Data collection was conducted by giving essay test adapted from Electromagnetic Concept Inventory test consisting of four major subconcepts namely: electrostatic, magnetics, electromagnetic induction and electromagnetic waves.  Data analysis was conducted by analyzing the test result data via the answer scale section and analysis of the interview results. The results of the study show interesting thing that the electrostatic subconcept is 3% for Bachelor?s Students of Physics Education and 6% for Master?s Students of Physics Education that answered questions correctly on the concept. In the sub-concept of electromagnetic waves, 7% of Bachelor?s Students of Physics Education and 6% for Master?s Students of Physics Education that answered correctly questions on the concept. The results indicate that most students ' cross-academic level difficulties were on electrostatic sub-concepts and electromagnetic waves that categorized the basic and upper concepts in magnetic electrical concepts. The results of the study give implications that the need to strengthen basic concepts and appropriate learning strategy in teaching the concept of magnetic electricity.